(untitled) - Zarowski, Christopher J. (Hoboken, NJ : Wiley, c2004, 2004)
This text is designed for engineers who are not afraid to wade through some fairly abstract math before reaching practical applications. This is not to say, however, that the coverage constitutes a rigorous treatment of the mathematical foundations of numerical analysis. Rather, this is very much a book for engineering students; and although some of the chapters, especially the early ones, have intimidating mathematical titles like functional analysis, orthogonal polynomials, and sequences and series, the examples are generally from engineering, and the most technical proofs are omitted. The author teaches electrical and computer engineering at the University of Alberta, so the examples tend to be drawn from that field; but the underlying techniques are applicable to all fields of engineering, and no background in electrical and computer engineering is required
Keywords: Electric engineering,Computer science,Numerical analysis; Mathematics,Mathematics